Endoglucanase activity in Neoteredo reynei (Bivalvia, Teredinidae) digestive organs and its content - de Moraes Akamine, Daniela Toma; de Almeida Cozendey da Silva, Daniel; de Lima Câmara, Gabriela; Carvalho, Thayane Vieira; Brienzo, Michel [UNESP] (Springer Nature, 2018)
Cellulolytic enzymes have been studied in several organisms, such as insects, molluscs and other organisms, which can have enzymes endogenously produced or by symbiotic microorganisms. These enzymes are responsible for breaking down the cellulosic material upon which these organisms feed, probably with the aim of assimilating the sugars and nutrients. As Teredinidae bivalves grown in mangrove trees, this study aimed to measure endo-β-1,4-glucanase activity in different organs and its content. Endo-β-1,4-glucanase activity was detected in different organs of the Teredinidae bivalves, including gills and digestive organs tissues and its content. Moreover, organisms such as teredinids grow up inside wood and this process could perhaps be related to creating growth space. All the endoglucanase extracts, from organs tissues and contents, showed maximum activity at 40 °C. The maximum activity was observed at pH 5.5 for all the extracts, except for intestine tissue, which maximum was at pH 6. Moreover, some of the extracts showed a different profile of the activity as a pH influence, suggesting different distribution of enzymes over the digestive system of the teredinids. The results suggested that the endo-β-1,4-glucanase from Teredinidae could be applied in process that requires low temperature, such as, simultaneous saccharification and fermentation, since it presents lower optimum temperature in comparison to enzymes from terrestrial microorganisms.
Keywords: Cellulases; Endo-β-1,4-glucanase; Optimum activity; Teredinidae; Wood digestion